Recombinant yeast TFIID, a general transcription factor, mediates activation by the gene-specific factor USF in a chromatin assembly assay. - Meisterernst, M (1990)
The TATA box-binding transcription factor TFIID from Saccharomyces cerevisiae was tested for its ability to mediate regulatory factor functions both in a cell-free system reconstituted with other general initiation factors (purified from HeLa cells) and in a combined nucleosome assembly-transcription system. In the latter assay recombinant yeast TFIID, expressed in and purified from bacteria, was sufficient to prevent nucleosome assembly-mediated repression and to mediate transcriptional enhancement of the adenovirus major late promoter by the gene-specific activator USF. In contrast, recombinant yeast TFIID was unable to mediate activation by USF in the system reconstituted only with purified general factors. Under the same conditions a partially purified natural yeast TFIID was able to mediate activation by both USF and Sp1 (assayed with the human immunodeficiency virus promoter), but to a lesser extent than observed with a partially purified natural human TFIID. The implications of these findings are discussed with respect to the structure of the yeast and human TATA factors and the possible involvement either of specific TFIID modifications or of coactivators.